Optimization of media components for chitinase production by chickpea rhizosphere associated Lysinibacillus fusiformis B‐CM18. (26th June 2012) - Singh, Rajesh Kumar; Kumar, D. Praveen; Solanki, Manoj Kumar; Singh, Pratiksha; Srivastva, Alok K.; Kumar, Sudheer; Kashyap, Prem L.; Saxena, Anil K.; Singhal, Pradeep K.; Arora, Dilip K.
Abstract Chitinase producing strain B‐CM18 was isolated from chickpea rhizosphere and identified as Lysinibacillus fusiformis B‐CM18. It showed in vitro antifungal activity against a wide range of fungal plant pathogens and was found to produce several PGPR activities. Further, a multivariate response surface methodology was used to evaluate the effects of different factors on chitinolytic activity and optimizing enzyme production. A central composite design was employed to achieve the highest chitinase production at optimum values of the process variables, viz., temperature (20–45 °C), sodium chloride (2–7%), starch (0.1–1%) and yeast extract (0.1–1%), added in the minimal medium supplemented with colloidal chitin (1–10%; w:w). The fit of the model (R2 = 0.5692) was found to be significant. The production medium to achieve the highest chitinase production (101 U ml−1) was composed of the minimal medium composed of chitin (6.09%), NaCl (4.5%), starch (0.55%) and yeast extract (0.55%) with temperature (32.5 °C). The results show that the optimization strategy led to an increase in chitinase production by 56.1‐fold. The molecular mass of the chitinase was estimated to be 20 kDa by anion exchange and gel filtration chromatography. Further, purified chitinase showed strong antifungal activity against test pathogens. Overall, these results may serve as a base line data for enhancing the chitinolytic potential of bacterial antagonists for bio‐management of chickpea pathogens.